2016
DOI: 10.1007/jhep07(2016)076
|View full text |Cite
|
Sign up to set email alerts
|

Rényi entropy and conformal defects

Abstract: We propose a field theoretic framework for calculating the dependence of Rényi entropies on the shape of the entangling surface in a conformal field theory. Our approach rests on regarding the corresponding twist operator as a conformal defect and in particular, we define the displacement operator which implements small local deformations of the entangling surface. We identify a simple constraint between the coefficient defining the two-point function of the displacement operator and the conformal weight of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
194
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(207 citation statements)
references
References 69 publications
(157 reference statements)
9
194
0
Order By: Relevance
“…The key ingredient in the study is the OPE of spherical twist operator [58][59][60] in terms of the primary operators in the replicated theory. This allows the systematic study of the mutual information.…”
Section: Jhep06(2017)096mentioning
confidence: 99%
“…The key ingredient in the study is the OPE of spherical twist operator [58][59][60] in terms of the primary operators in the replicated theory. This allows the systematic study of the mutual information.…”
Section: Jhep06(2017)096mentioning
confidence: 99%
“…This conjecture has passed numerical test for free scalar and free fermion [17]. According to [12], it seems that the relation (1.8) holds only for free CFTs. Evidence includes an analytic proof for free scalar.…”
Section: Jhep12(2016)036mentioning
confidence: 92%
“…It is found that entanglement plays an important role in the emergence of space-time and gravitational dynamics [1][2][3][4][5]. In addition to entanglement entropy, Rényi entropy has drawn much attention recently, including the holographic formula of Rényi entropy [6,7], the shape dependence of Rényi entropy [8][9][10], the holographic dual of boundary cones [11] and Rényi twist displacement operator [12,13].…”
Section: Jhep12(2016)036mentioning
confidence: 99%
See 2 more Smart Citations